1984
DOI: 10.1111/j.1365-2605.1984.tb00805.x
|View full text |Cite
|
Sign up to set email alerts
|

Carnitine and acetylcarnitine in motile and immotile human spermatozoa

Abstract: Human sperm were found to contain acetylcarnitine, carnitine, and only traces of propionylcarnitine and four-carbon acylcarnitines. Carnitine and acetylcarnitine were present in higher concentrations in sperm than in the corresponding seminal fluid samples, and the degree of acylation of carnitine was greater in sperm than in seminal plasma. The ratio of acetylcarnitine/carnitine was 1.77 +/- 0.69 in extracts of sperm from samples with a low degree of motility (0-10% motile), whereas it was 4.70 +/- 1.58 in sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
2
2

Year Published

1986
1986
2012
2012

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 25 publications
1
19
2
2
Order By: Relevance
“…Indeed, a close relationship exists between motility and the cellular carnitine content and its acetylation state (56,57). Statistical positive correlation had been found between seminal carnitine and total sperm motility in fertile (58) and infertile men (59)(60)(61).…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, a close relationship exists between motility and the cellular carnitine content and its acetylation state (56,57). Statistical positive correlation had been found between seminal carnitine and total sperm motility in fertile (58) and infertile men (59)(60)(61).…”
Section: Discussionmentioning
confidence: 96%
“…Other experiments have indicated that the acylation state of carnitine may be correlated with the ability of spermatozoa to move. Johansen & Böhmer (1979) and Golan, Weissenberg & Lewin (1984) have demonstrated that the degree of acetylation of carnitine is greater in motile than in immotile human spermatozoa. Tanphaichitr (1977) and Jeulin, Soufir & Jouannet (1981) have reported that addition of acetylcarnitine to ejaculated human spermatozoa stimulated motility slightly.…”
Section: Introductionmentioning
confidence: 97%
“…Carnitine involvement in energy metabolism has been extensively studied in tissues such as liver (Hulse and Henderson 1980), skeletal muscle (Cederblad et al 1976), heart (Bahl et al 1981), kidney (Huth and Shug 1980), brain (Natecz and Natecz, 1996), serum , lymphocytes (Alhomida 2000), urine (Al-Kholaifi and Alhomida 1999), milk (Alhomida 1996) and sperm (Golan et al 1984). A study in our laboratory showed that the concentrations of carnitine in the Arabian camel tissues are higher than in most other species and a higher proportion of acyl carnitine compared to free carnitine exists in plasma and skeletal muscle (Alhomida et al 1995a).…”
Section: Introductionmentioning
confidence: 99%